SCREENING FOR ELDERLY PEOPLE EXPERIENCING MALNUTRITION BASED ON THE MINI NUTRITIONAL ASSESSMENT (MNA) AT BATAM CITY NURSING HOMES IN DECEMBER 2022 - Rahayu Yekti; Arvin Hardian Tambunan; Pratiwi Dyah Kusumo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Malnutrition refers to a condition when the body does not get enough of the necessary nutritional intake. Malnutrition in the elderly is a serious global health problem due to changes in the age pyramid throughout the world, especially the proportion of the number of elderly. The elderly are vulnerable to functional disorders, nutritional intake and economic problems. psychological and motoric As a result, it is very easy for elderly people to experience a decrease in nutritional intake which triggers nutritional problems and other disorders in the elderly. This research uses the Mini Nutritional Assessment (MNA) questionnaire to identify the nutritional status of the elderly and its relationship with elderly screening including food intake, as well as several disorders (mobility, psychological, neurological) in the elderly at Batam City Nursing Homes in December 2022. The research method used is descriptive analytic with a cross-sectional approach, the research sample consists of 65 respondents selected using total sampling techniques. The research results showed that based on the Mini Nutritional Assessment, 10 respondents (15.4%) had normal nutritional status, 30 people (46.2%) were at risk of experiencing malnutrition, and 25 people (38.5%) experienced malnutrition. The majority of elderly people experience a decrease in food intake, are still able to move (mobility), do not experience psychological disorders, but the majority have experienced neurological disorders (dementia).